Estabelecimento de métodos moleculares para detecção de Mycobacterium leprae como ferramenta de diagnóstico para hanseníase - Albuquerque, Andressa Almeida (2024)
Leprosy is a chronic infectious disease caused by the bacillus Mycobacterium leprae. As it is a pathology that presents a long time for incubation, children diagnosed with leprosy indicate active transmission in the community. Leprosy skin lesions, which can be easily confounded with other diseases, and the subjectivity of dermatoneurological evaluation, reveal the need for laboratory tests that could assist in the diagnosis, making it less subjective and, thus, minimizing risks and challenges related to late diagnosis. The objective of the present study was to establish methods for detecting M. leprae DNA by molecular biology to identify groups at risk for the development of leprosy contacts under 15 years of age and its association with results of dermatoneurological evaluation and with positivity of serum antibodies to the phenolic glycolipid antigen 1 (PGL1), specific to M. leprae. Two types of real-time PCR (qPCR) techniques were validated for detecting M. leprae DNA in blood samples, that is, Sybr green and Taqman®. The commercial NATHANS-Leprosy kit, recently approved for use with skin biopsy samples, was also used to analyze DNA samples extracted from whole blood. 56 index cases and 317 contacts under the age of 15 living in Santana do Ipanema (AL), São Gonçalo do Amarante (CE) and Canindé (CE) were selected. After dermatoneurological evaluation, whole blood samples were collected for detection of M. leprae DNA by qPCR and serum for anti-PGL1 measurement by indirect ELISA. The targets chosen for qPCR were the 16SrRNA and RLEP genes. An RLEP genetic sequence designed from the Primer Express 3.0 Program was also used. The tests for RLEP and 16S rRNA showed analytical sensitivities of 1.57 fg/µL and 97.66 fg/µL. While the tests for RLEP showed analytical specificity to M. leprae DNA, 16S rRNA also showed amplification to DNA from other mycobacteria. Nonetheless, 16S rRNA in Taqman® tests presented specificity to M. leprae DNA. All tests performed as expected for PCR amplification curves. When they were applied to DNA samples extracted from contacts and cases, there was no correlation between serology and molecular tests. Among the molecular tests, the NATHANS-Leprosy kit shows a slight correlation with the Taqman® and Sybr Green tests. In conclusion, in the present work it was possible to establish two molecular methods for Mycobacterium leprae DNA that proved to be sensitive, specific and reproducible using two RLEP sequences and one 16S rRNA sequence. However, they cannot yet be considered validated for use with whole blood samples, as the current study showed a complete discrepancy among the methods.